Laminate of conductor and insulating coating film, coil, rotating electrical machine, insulating resin composition, insulating coating material, and insulating film

By using an insulating film made of nanocomposite materials in insulated wires, the problem of local discharge in insulated wires is solved, and excellent local discharge resistance and insulation characteristics are achieved, and the service life of the insulating layer is extended.

CN119895504APending Publication Date: 2025-04-25SUMITOMO SEIKA CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380066792.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-27
Filing Date
2023-10-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In high humidity environments, insulated wires are prone to partial discharge, resulting in insulation damage. Especially in the case of inverter surges, the insulation characteristics are reduced and durability is insufficient.

Method used

An insulating film composed of nanocomposite materials includes a resin composition in which metal oxide hydrate is dispersed in the resin. The Zeta potential of the metal oxide hydrate when dispersed in N-methyl-2-pyrrolidone (NMP) is negative, thereby improving the local discharge resistance and insulation characteristics of the insulating layer.

Benefits of technology

Even in a high humidity environment, the partial discharge resistance and insulation characteristics of the laminated body are significantly excellent, which extends the service life of the insulating layer and reduces the possibility of insulation damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895504A_ABST
    Figure CN119895504A_ABST
Patent Text Reader

Abstract

Provided is a laminate having excellent partial discharge resistance and excellent insulation characteristics even in a high-humidity environment. The present invention relates to a laminate having at least a conductor and an insulating coating film, the insulating coating film comprising a nanocomposite material containing a resin composition in which a metal oxide hydrate having a negative Zeta potential when dispersed in N-methyl-2-pyrrolidone (NMP) is dispersed in a resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] In one aspect, the present invention relates to a laminate of a conductor and an insulating film, a coil, a rotating electric machine, an insulating resin composition, an insulating coating, and an insulating film. Background Art

[0002] As an insulated wire used in electrical equipment such as motors, an insulated wire in which an insulating coating obtained by dissolving a resin or a resin precursor such as polyimide or polyamideimide in an organic solvent is applied to the surface of a conductor and baked (Japanese: 焼付け) to form an insulating layer can be used; an insulated wire in which an insulating film such as a polyimide film or a mica tape is wound around a conductor to form an insulating layer (so-called tape winding).

[0003] In electronic devices with a high operating voltage, such as motors used at high voltages, if a high voltage is applied to the insulated wires constituting the coil and there are minute voids between adjacent insulated wires or in the insulating film, electric field concentration may occur in this part and partial discharge may occur. There are problems such as deterioration occurring in the insulating film due to such partial discharge, early insulation breakdown of the coil, and damage to the electronic device.

[0004] In addition, in recent years, in systems that drive motors and the like through an inverter used for energy saving and variable speed, in devices classified as low-voltage drive, overvoltages (so-called inverter surges) that are sharp with respect to the drive voltage are also generated repeatedly in a very short time, and the number of cases where insulation breakdown occurs has increased. This insulation breakdown is caused by partial discharge due to the overvoltage repeatedly generated by the inverter surge.

[0005] As a method for improving the resistance to this partial discharge (partial discharge resistance property), a resin composition containing a metal oxide hydrate such as boehmite in nanosize has been disclosed as a laminate of an insulating film (for example, refer to Patent Document 1).

[0006] Prior Art Documents Patent Documents Patent Document 1: Japanese Patent No. 6567797 Summary of the Invention

[0007] Technical Problem to be Solved by the Invention Many motors are used in harsh environments, such as high-humidity environments. Generally, in a high-humidity environment, the partial discharge inception voltage decreases and partial discharge is likely to occur, so it is required to maintain performance even in a high-humidity environment. In addition, generally, when the insulating layer absorbs moisture, the insulation breakdown voltage also decreases. Further, when an inorganic substance such as a metal oxide hydrate is mixed in the insulating layer to improve the partial discharge resistance, the flexibility also decreases.

[0008] In one aspect, an object of the present invention is to provide a laminate having excellent partial discharge resistance and excellent insulation properties even in a high-humidity environment. Further, an object of the present invention is also to provide a coil, a rotating electric machine, an insulating resin composition, an insulating coating, and an insulating film that have excellent partial discharge resistance and excellent insulation properties even in a high-humidity environment, and an insulating resin composition, an insulating coating, and an insulating film for forming the laminate.

[0009] Technical solutions for solving technical problems The inventors of the present invention have conducted intensive research to solve the above problems. As a result, the following unexpected insights have been obtained: a laminate having at least a conductor and an insulating film, the insulating film being composed of a nanocomposite material, the nanocomposite material including a resin composition in which a metal oxide hydrate is dispersed in a resin, and using, as the metal oxide hydrate, a substance having a negative Zeta potential when dispersed in N-methyl-2-pyrrolidone (NMP), whereby the laminate has excellent partial discharge resistance and excellent insulation properties in a high-humidity environment. The present invention has been completed by further repeated research based on the above insights.

[0010] In one aspect, the present invention provides the following laminate, coil, rotating electric machine, insulating resin composition, insulating coating, and insulating film.

[0011] Item 1. A laminate having at least a conductor and an insulating film, wherein the insulating film is composed of a nanocomposite material, the nanocomposite material including a resin composition in which a metal oxide hydrate is dispersed in a resin, and the metal oxide hydrate has a negative Zeta potential when dispersed in N-methyl-2-pyrrolidone (NMP).

[0012] Item 2. The laminate according to Item 1, wherein the metal oxide hydrate includes aluminum oxide hydrate.

[0013] Item 3. The laminate according to Item 1 or 2, wherein the nanocomposite material is formed by dispersing the metal oxide hydrate in a sol state.

[0014] Item 4. The laminate according to any one of Items 1 to 3, wherein the resin contained in the nanocomposite material is at least one selected from formaldehyde resin, polyurethane, epoxy resin, polyester, polyesterimide, polyetherimide, polyamideimide, polyimide, and their precursors.

[0015] Item 5. The laminate according to any one of Items 1 to 4, wherein the resin contained in the nanocomposite material is at least one selected from polyimide and precursors of polyimide.

[0016] Item 6. The laminate according to any one of Items 1 to 5, wherein the laminate is in the form of an insulated wire.

[0017] Item 7. A coil comprising the laminate according to Item 6.

[0018] Item 8. A rotating electrical machine comprising the laminated body according to Item 6.

[0019] Item 9. An insulating resin composition for forming the insulating film of the laminated body according to any one of Items 1 to 5.

[0020] Item 10. An insulating coating material for forming the insulating coating of the laminate according to any one of Items 1 to 5.

[0021] Item 11. An insulating film formed from the nanocomposite material according to any one of Items 1 to 5.

[0022] Effects of the Invention According to one aspect of the present invention, there can be provided a laminated body having at least a conductor and an insulating film, which has excellent partial discharge resistance and excellent insulation properties even in a high humidity environment. In addition, according to one aspect of the present invention, there can be provided a coil and a rotating electric machine having excellent partial discharge resistance and excellent insulation properties even in a high humidity environment, and an insulating resin composition, an insulating coating, and an insulating film for forming the laminated body. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic cross-sectional view showing an example of a laminated body according to an embodiment of the present invention.

[0024] Figure 2 This is a schematic cross-sectional view showing an example of an insulated wire according to an embodiment of the present invention.

[0025] Figure 3 This is a schematic cross-sectional view showing another example of the insulated wire according to the embodiment of the present invention.

[0026] Figure 4 This is a schematic cross-sectional view showing another example of the insulated wire according to the embodiment of the present invention.

[0027] Figure 5 This is a schematic cross-sectional view showing another example of the insulated wire according to the embodiment of the present invention. DETAILED DESCRIPTION

[0028] Hereinafter, several embodiments of a laminate, a coil, a rotating electrical machine, an insulating resin composition, an insulating coating, and an insulating film according to one aspect of the present invention are described in detail. It should be noted that in this specification, a numerical value connected with "-" refers to a numerical range including the numerical values ​​before and after "-" as a lower limit and an upper limit. When multiple lower limits and multiple upper limits are recorded separately, any lower limit and upper limit can be selected and connected with "-".

[0029] The laminate of the present invention is a laminate having at least a conductor and an insulating film formed on the conductor. In the laminate involved in the embodiment of the present invention, the insulating film is composed of a nanocomposite material (i.e., a composite material in which nano-sized metal oxide hydrates are dispersed in a resin), and the nanocomposite material includes a resin composition in which metal oxide hydrates are dispersed in a resin, and the zeta potential of the metal oxide hydrates when dispersed in N-methyl-2-pyrrolidone (NMP) is negative. The laminate involved in the embodiment of the present invention has such a structure, and has excellent partial discharge resistance even in a high-humidity environment and excellent insulation properties. Referring to the following, Figure 1~5 The laminated body according to the embodiment of the present invention will be described in detail.

[0030] It should be noted that in the present invention, "inverter surge" refers to a sharp overvoltage that overlaps with the drive voltage and is generated by the switching of the inverter. The switching frequency of the inverter reaches 100kHz at high speed from a relatively slow 1kHz, so the frequency of inverter surge also reaches an extremely high frequency of 100kHz from about 1kHz. In addition, regarding the voltage, it starts from about 1000V when overlapping with the drive voltage of the industrial inverter motor, that is, 400V, to a voltage of about 3kV overlapping with the operating voltage of the high-voltage drive inverter motor.

[0031] like Figure 1 to Figure 5 As shown in FIG. 1 , the laminated structure of the laminated body 10 according to the embodiment of the present invention is a laminated body having at least a conductor 1 and an insulating film 2. Specifically, the laminated body 10 of the present invention is, for example, Figure 1 As shown in FIG. 1 , the laminate 10 according to the embodiment of the present invention may be in the form of a film having at least a conductor 1 and an insulating film 2 laminated on the conductor 1. Figure 2~5 As shown, it may be in the form of an insulated wire having a conductor 1 at the center portion and an insulating film 2 formed on the periphery of the conductor 1. When the laminate 10 of the present invention is made into the form of an insulated wire, the cross-sectional shape may be circular, elliptical, polygonal (may be rectangular or irregular), etc. Figure 2~4 In FIG. 1 , an insulated wire having a circular cross section is shown. In addition, Figure 5, an insulated wire having a substantially quadrilateral cross section is shown. When the cross-sectional shape of the conductor 1 is circular, the diameter is, for example, about 0.03 to 4.0 mm.

[0032] The laminated structure of the laminated body 10 according to the embodiment of the present invention only needs to include at least the conductor 1 and the insulating film 2, and may include other layers. Examples of the other layers include insulating layers 3 and 4. For example, Figure 3 , a laminated body 10 (insulated wire) including a conductor 1, an insulating film 2 formed on the upper surface thereof, and an insulating layer 3 further formed on the upper surface thereof is shown. Figure 4 , 5 , a laminated body 10 (insulated wire) is shown, which includes a conductor 1, an insulating layer 4 formed on the upper surface thereof, an insulating film 2 formed on the upper surface of the insulating layer 4, and an insulating layer 3 further formed on the upper surface of the insulating film 2. It should be noted that as a material constituting the insulating layers 3 and 4, a resin having heat resistance (heat-resistant resin) and the like described later can be cited.

[0033] The insulating layers 3 and 4 may each be made of the same material as the insulating film 2, or may be made of other materials. In addition, the insulating layers 3 and 4 may each be made of the same material, or may be made of other materials. In addition, the insulating layers 3 and 4 may each be provided below the insulating film 2 (i.e., on the conductor 1 side), or may be provided above the insulating film 2 (i.e., on the opposite side to the conductor 1 side).

[0034] In addition, examples of other layers include a plating layer formed between the conductor surface and the insulating layer and made of a metal different from that of the conductor.

[0035] The conductor 1 may be made of any conductive material, including copper (low-oxygen copper, oxygen-free copper, copper alloy, etc.), aluminum, silver, nickel, iron, etc. The conductor 1 may be made of any material that is conductive, and the material may be selected appropriately according to the application of the present invention.

[0036] As described above, the insulating film 2 is composed of a nanocomposite material, which includes a resin composition in which a metal oxide hydrate is dispersed in a resin. From the viewpoint of appropriately exerting the effect of the present invention, as the metal oxide hydrate, an aluminum oxide hydrate such as boehmite and gibbsite is preferred. The metal oxide hydrate contained in the insulating film 2 is preferably boehmite. In addition, the metal oxide hydrate may be one kind or two or more kinds.

[0037] In addition, regarding the shape of the metal oxide hydrate, from the aspect of better resistance to partial discharge characteristics, it is preferably a flat particle with a large aspect ratio (long side (one side) / thickness). The shape of the metal oxide hydrate is preferably plate-shaped, rod-shaped, needle-shaped, etc. In addition, the shape when looking down at the main surface of the metal oxide hydrate (usually the surface in the direction perpendicular to the thickness direction) is preferably a roughly rectangular (roughly square, roughly rectangular, etc., roughly quadrilateral) etc. The aspect ratio (long side (one side) / thickness) of the metal oxide hydrate is preferably 4 or more, more preferably 10 or more, and further preferably 15 or more, and preferably 200 or less, more preferably 100 or less, and further preferably 50 or less. It should be noted that the aspect ratio in this specification refers to the ratio obtained by observation at a magnification of 5000 times using a scanning electron microscope.

[0038] The metal oxide hydrate is preferably in the form of particles, and the average particle size of the metal oxide hydrate particles is preferably 100 nm or less, more preferably 80 nm or less, and further preferably 50 nm or less. It should be noted that the lower limit of the average particle size of the metal oxide hydrate particles is, for example, 5 nm or more, preferably 10 nm or more. As a preferred range of the average particle size of the metal oxide hydrate particles, 5 to 100 nm, 5 to 80 nm, 5 to 50 nm, 10 to 100 nm, 10 to 80 nm, 10 to 50 nm, etc. can be cited. When the metal oxide hydrate particles are flat particles with a large aspect ratio (long side (one side) / thickness) as described above, the average value of the long side and the short side is taken as the average particle size by observation under a scanning electron microscope.

[0039] In the present invention, the Zeta potential of the metal oxide hydrate when dispersed in N-methyl-2-pyrrolidone (NMP) is negative. By using the nanocomposite material of the metal oxide hydrate with negative Zeta potential for the insulating film, the laminated body involved in the embodiment of the present invention can exert excellent partial discharge resistance and excellent insulation properties in a high humidity environment. Regarding the mechanism of exerting these characteristics, for example, it can be considered as follows. That is, it is believed that the resin generally has functional groups such as carboxyl, aldehyde, ether, ester, amino, amide, and hydroxyl groups, and the surface of the resin has a negative surface charge due to the generation of hydroxyl, amino, etc. derived from the polarization, local hydrolysis, etc. of these functional groups. It is believed that if the metal oxide hydrate of the present application is dispersed in these resins, the resin and the metal oxide hydrate are repelled. It is speculated that through this repulsion, the molecular vibration of the resin chain is further suppressed, and as a result, these characteristics are exerted.

[0040] The zeta potential of the metal oxide hydrate may be a negative value. From the viewpoint of more appropriately exerting the effect of the present invention, the absolute value of the zeta potential of the metal oxide hydrate is preferably 1 to 100 mV, more preferably 2 to 50 mV, further preferably 3 to 30 mV, further preferably 5 to 25 mV, further preferably 5 to 10 mV.

[0041] The Zeta potential of the metal oxide hydrate is measured by the following method. First, the metal oxide hydrate is diluted with N-methyl-2-pyrrolidone (NMP) in a sol state, and the concentration is adjusted to 0.1% by mass to prepare a sample. Next, the sample is placed in a constant temperature bath at 5°C and kept warm for 1 hour. Then, about 1g of the sample is filled in the Zeta potential insertion sample cell (Zeta Dip Cell) for measurement, and the measurement is carried out. The measuring device uses the ZetasizerNano ZS manufactured by Malvern. The specific measurement is based on the method described in the embodiment.

[0042] From the viewpoint of more appropriately exerting the effect of the present invention, the metal oxide hydrate is preferably surface treated. As a surface treatment method, for example, there is a method using a surface treatment agent, specifically, a method of treating with a silane coupling agent (epoxy silane coupling agent, methacrylic silane coupling agent, etc.), a method of treating with a titanate coupling agent, a method of treating with an aluminate surface treatment agent, a method of treating with a phosphoric acid surface treatment agent, a method of treating with a carboxylic anhydride such as phthalic anhydride, etc. Among them, preferably, a metal oxide hydrate surface treated with a silane coupling agent, a metal oxide hydrate surface treated with a phosphoric acid surface treatment agent, and more preferably a metal oxide hydrate surface treated with a phosphoric acid surface treatment agent. Examples of phosphoric acid-based surface treatment agents include phenylphosphonic acid, octadecylphosphonic acid, 11-{2-[2-(2-methoxyethoxy)ethoxy]ethoxy}undecylphosphonic acid, 1H,1H,2H,2H-perfluoro-n-decylphosphonic acid, 1H,1H,2H,2H-perfluoro-n-hexylphosphonic acid, 11-hydroxyundecylphosphonic acid, 10-carboxydecylphosphonic acid, 11-aminoundecylphosphonic acid and other phosphonic acid derivative-based surface treatment agents. Among phosphoric acid-based surface treatment agents, metal oxide hydrates surface-treated with the above-described phosphonic acid derivative-based surface treatment agents can have a suitable negative zeta potential and are particularly suitable as metal oxide hydrates that exert the effects of the present invention.

[0043] The surface treatment method is not particularly limited. When the metal oxide hydrate is a powder, a method of spraying a solution obtained by dissolving a surface treatment agent in a solvent onto the powder by spraying or the like, followed by drying at 20 to 60° C., and when a metal oxide hydrate sol is used, a method of adding a surface treatment agent, dissolving the surface treatment agent, and stirring at 20 to 60° C. for 1 to 24 hours can be used. It should be noted that when the metal oxide hydrate is treated with a surface treatment agent, the amount of the surface treatment agent used is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 40 parts by mass or less, relative to 100 parts by mass of the metal oxide hydrate.

[0044] The resin contained in the resin composition (nanocomposite material) constituting the insulating film 2 is preferably a heat-resistant resin. That is, the insulating film 2 is formed by applying and sintering the insulating coating (resin composition containing metal oxide hydrate) used in the formation of the insulating film 2, so excellent heat resistance is required. As a heat-resistant resin, as long as it is a resin with excellent heat resistance, the resin used in the known insulated wires, etc. can be used. As heat-resistant resins, for example, formal resins, polyurethanes, epoxy resins, polyesters, polyamides, polyester imides, polyether imides, polyamide-imides, polyimides, and their precursors can be cited. Among these, from the viewpoint of further improving heat resistance, polyester imides, polyamide-imides, polyimides and their precursors are preferred, and polyimides and polyimide precursors are further preferably used. The resin contained in the insulating film 2 can be one kind or two or more kinds.

[0045] In addition, in the resin composition constituting the insulating film 2, the lower limit of the resin content is preferably 50 mass % or more, more preferably 60 mass % or more, and the upper limit is preferably 97 mass % or less, more preferably 90 mass % or less, and further preferably 85 mass % or less.

[0046] In addition, in the resin composition constituting the insulating film 2, the lower limit of the content of the metal oxide hydrate is preferably 3 mass % or more, more preferably 10 mass % or more, and further preferably 12 mass % or more, and the upper limit is preferably 50 mass % or less, and more preferably 40 mass % or less.

[0047] In addition, in the resin composition constituting the insulating film 2, as a ratio (mass ratio) of the resin to the metal oxide hydrate, the metal oxide hydrate is preferably 1 to 50 parts by mass, more preferably 2 to 30 parts by mass, further preferably 3 to 25 parts by mass, and further preferably 15 to 25 parts by mass, relative to 100 parts by mass of the total of the resin and the metal oxide hydrate.

[0048] From the viewpoint of further appropriately exerting the effect of the present invention, the thickness of the insulating film 2 is preferably 3 m m or more, more preferably 5 m m or more, more preferably 10 m It should be noted that the upper limit of the thickness of the insulating film 2 is preferably 200 m. m m or less, more preferably 100 m m or less, more preferably 50 m m or less.

[0049] Furthermore, when preparing the insulating coating material to be described later for forming the insulating film 2 , the resin and the metal oxide hydrate may be used in a form (resin varnish or the like) in which they are dissolved or dispersed in a solvent, respectively.

[0050] When preparing the insulating coating material to be described later for forming the insulating film 2, it is preferred to prepare the insulating coating material in which the resin is dissolved or dispersed in the solvent and the metal oxide hydrate is dispersed, and then apply and bake the insulating coating material to form the insulating film 2. As a solvent for dissolving or dispersing the resin and appropriately dispersing the metal oxide hydrate, it is preferred to use phenols mainly composed of cresol, aromatic alcohols, NMP (N-methyl-2-pyrrolidone), DMAC (N,N-dimethylacetamide), DMF (N,N-dimethylformamide), DMI (1,3-dimethyl-2-imidazolidinone), carbonate solvents, lactone solvents, glycol ethers, etc., which are mainly high-boiling point solvents. As a manufacturing method for preparing the insulating coating material, for example, a method of manufacturing using conventional known mixing devices such as a kneader, a pressure kneader, a mixing roll, a Banbury mixer, a twin-screw extruder, a rotation and revolution mixer, and a homogenizer. As the mixing temperature at this time, it is usually 5 to 30°C.

[0051] For dispersion stabilization, the insulating coating may contain an acid component or an alkaline component. Similarly, water, low-boiling alcohol, or a low-viscosity solvent that helps reduce the viscosity of the insulating coating may also be contained. It should be noted that, in the insulating coating, other metal oxide hydrates and metal oxides may be mixed as needed, and additives may be added for hydrophobicity and dispersibility improvement. As the additive, fluorine-based and silicon-based additives, citric acid, ethylenediaminetetraacetic acid and 8-hydroxyquinoline are preferably used.

[0052] As described above, the laminated body 10 involved in the embodiment of the present invention may be composed of only the conductor 1 and the insulating film 2, or may further have other layers such as the insulating layer 3 and the insulating layer 4. As other layers, for example, an organic insulating layer may be cited. The organic insulating layer is preferably composed of the heat-resistant resin. That is, in the organic insulating layer, as specific examples of the heat-resistant resin, formal resin, polyurethane, epoxy resin, polyester, polyamide, polyesterimide, polyetherimide, polyamideimide, polyimide, and their precursors may be cited. Among them, from the viewpoint of further improving heat resistance, polyesterimide, polyamideimide, polyimide and their precursors may be preferably used. The heat-resistant resin contained in the organic insulating layer may be one kind or more than two kinds. In addition, a metal layer such as a plating layer may also be formed on the conductor 1.

[0053] From the viewpoint of further appropriately exerting the effects of the present invention, the total thickness of the insulating layer of the laminate 10 according to the embodiment of the present invention is preferably 5 m m or more, more preferably 10 m m or more, more preferably 20 m It should be noted that the upper limit of the thickness of the organic insulating layer is preferably 200 m. m m or less.

[0054] By exposing the laminated body according to the embodiment of the present invention to partial discharge caused by inverter surge, an inorganic insulating layer is formed on a portion of the insulating film 2. Patent Document 1 also discloses forming a 100 nm to 50 nm thick laminated body by partial discharge. m m, which helps to extend the life of the power supply. In the present invention, the inorganic insulating layer is formed even when it absorbs moisture in a high humidity environment. It is believed that this helps to extend the life of the power supply even when it absorbs moisture. The inorganic insulating layer is formed, for example, at a frequency of 1kHz to 100kHz and a voltage of 600V to 3kV.

[0055] The laminate 10 according to the embodiment of the present invention can be manufactured by stacking layers constituting the insulating film 2 on the conductor 1. For example, it can be manufactured by coating and baking a resin composition forming the insulating film 2 on the conductor 1. In addition, an insulating film formed by a resin composition forming the insulating film 2 can be wound around the outer periphery of the conductor 1 to manufacture an insulated wire. The insulating film can be formed by, for example, molding and calcining the resin composition (insulating coating) forming the insulating film 2 using a film coater or the like. The difference in the manufacturing methods of these insulated wires is whether the insulating film 2 is formed on the conductor or the insulating film is formed separately and then wound on the conductor 1. The insulating film is formed by forming the insulating film 2 in the form of a film.

[0056] Regarding the coating method of the insulating coating, there are examples of coating methods using a coating machine, methods of repeatedly coating and drying by a dip coater or a mold to obtain a film of a specified thickness, and coating by spraying, etc., which are not particularly limited. In addition, baking can be performed by, for example, heating at a high temperature (for example, above 300° C.) for a specified time. Furthermore, the formation of the insulating film 2 can also be performed by repeating a series of operations of coating and heating multiple times until the insulating film 2 reaches a specified thickness. It should be noted that in the formation of the insulating film 2, the baking temperature and time are set to a temperature and time at which the metal oxide hydrate will not be degenerated into other metal oxide hydrates or metal oxides due to heat, depending on the type of metal oxide hydrate.

[0057] For example, if the laminate 10 according to the embodiment of the present invention is formed into an insulated wire, an insulating coating material may be applied to the surface of the conductor 1 in the shape of a wire and then baked to produce the insulated wire. The insulating film 2 may be formed by repeatedly applying the insulating coating material to the conductor 1 with a predetermined thickness for a plurality of times (e.g., 10 to 20 times) and heating the conductor 1 at a high temperature (e.g., 300 to 500° C.) for a predetermined time (e.g., 1 to 2 minutes) until the insulating film 2 reaches a predetermined thickness.

[0058] The coil according to the embodiment of the present invention can be formed by winding the insulating wire around a core. In addition, in the rotating electric machine according to the embodiment of the present invention, the coil according to the embodiment of the present invention is used for a motor or the like. That is, the rotating electric machine according to the embodiment of the present invention may be a rotating electric machine made using the insulating wire according to the embodiment of the present invention, or may be a rotating electric machine made by forming an insulating film 2 on the surface of the conductor 1 after forming the rotating electric machine using the conductor 1, thereby forming an insulating wire.

[0059] Examples of the rotating electrical machine include a motor and a generator.

[0060] Example Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0061] The resins (polyimide coating materials) used in Examples and Comparative Examples are as follows.

[0062] [Resin (polyimide coating)] Pyre-MLRC5019 manufactured by IST Co., Ltd. was used.

[0063] [Insulating coating containing metal oxide hydrate] Insulating coating materials having the compositions shown in Table 1 were prepared according to the procedures shown in the following Production Examples 1 to 4.

[0064] <Production Example 1> In the polyimide coating, with respect to 85 parts by mass of the resin component, 15 parts by mass of boehmite calculated as alumina was used, and NMP-dispersed phosphoric acid-based surface-treated boehmite sol [product name: Alumina Sol A2M7 (containing 7% by mass of boehmite), average particle size: 15 to 50 nm, aspect ratio (long side / thickness): 10 to 50, manufactured by Kawaken Fine Chemicals Co., Ltd.] was stirred for 5 minutes at room temperature using a homogenizer to uniformly disperse it, thereby obtaining an insulating coating 1.

[0065] <Production Example 2> Insulating varnish 2 was obtained in the same manner as in Production Example 1, except that 87 parts by mass of the resin component and 13 parts by mass of boehmite were used in terms of alumina.

[0066] <Production Example 3> Insulating coating 3 was obtained in the same manner as in Manufacturing Example 1 except that NMP-dispersed methacrylic silane coupling agent surface-treated boehmite sol [product name: Alumina Sol 5SK-5-10 (containing 10% by mass of boehmite), average particle size: 20 nm, aspect ratio (long side / thickness): 4 to 20, manufactured by Kawaken Fine Chemicals Co., Ltd.] was used instead of alumina sol A2M7 in such a way that 5 parts by mass of boehmite was calculated as alumina.

[0067] <Production Example 4> To an NMP-dispersed boehmite sol [product name: Alumina Sol A1-10 (containing 10% by mass of boehmite), average particle size: 15 to 50 nm, aspect ratio (long side / thickness): 10 to 50, manufactured by Kawaken Fine Chemicals Co., Ltd.] were added 6 parts by mass of ethyl phosphate (acid ethyl phosphate [Ethyl Phosphate, a mixture of monoester and diester (Mono- and Di-Ester mixture, manufactured by Tokyo Chemical Industry, monoester content 35.0 to 47.0%, diester content 53.0 to 67.0%)] relative to 100 parts by mass of boehmite (calculated as alumina) and 24 parts by mass of 8-hydroxyquinoline (manufactured by Tokyo Chemical Industry) relative to 100 parts by mass of boehmite (calculated as alumina), and the mixture was stirred at room temperature for 1 hour to obtain an NMP-dispersed boehmite sol containing ethyl phosphate surface-treated boehmite.

[0068] Next, the ethyl phosphate surface-treated boehmite sol was uniformly mixed and dispersed at room temperature using an in-line homomixer so that 15 parts by mass of boehmite in terms of alumina was contained in the polyimide coating material relative to 85 parts by mass of the resin component, thereby obtaining an insulating coating material 4 .

[0069] <Production Example 5> Insulating coating material 5 was obtained in the same manner as in Production Example 4 except that 10 parts by mass of phenylphosphonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of 6 parts by mass of ethyl phosphate.

[0070] <Production Example 6> Insulating coating material 6 was obtained in the same manner as in Production Example 5, except that the amount of phenylphosphonic acid was changed from 10 parts by mass to 30 parts by mass.

[0071] <Production Example 7> Insulating coating material 7 was obtained in the same manner as in Production Example 5, except that the amount of phenylphosphonic acid was changed from 10 parts by mass to 40 parts by mass.

[0072] [Measurement of Zeta Potential of Metal Oxide Hydrate] The Zeta potential of the surface-treated boehmite used in the preparation of the insulating coating obtained in Manufacturing Examples 1 to 7 was measured by the following method. The surface-treated boehmite was diluted with N-methyl-2-pyrrolidone in the state of NMP-dispersed sol, and the concentration was adjusted to 0.1% by mass. It should be noted that when the boehmite is a powder, the powder is added to N-methyl-2-pyrrolidone, and the powder is dispersed in a wet jet mill Star Burst manufactured by Sugino Machinery Co., Ltd. to make a sol, and then the concentration is adjusted to 0.1% by mass. Then, the adjusted sample is placed in a thermostatic bath at 5°C and kept warm for 1 hour. Then, about 1g of the sample is filled in the Zeta potential insertion sample cell (Zeta Dip Cell) for measurement, and the measurement is carried out. The measuring device uses the Zetasizer Nano ZS manufactured by Malvern. The measurement conditions are as follows. In addition, the Zeta potential of each boehmite is shown in Table 1.

[0073] ·Sample: Boehmite, refractive index 1.65, absorptivity 0.008 Dispersion medium: N-methyl-2-pyrrolidone Viscosity 1.89 Refractive index 1.470 Dielectric constant 32.0 Equilibration time: 120 seconds F (Ka): 1.5 [Production of insulating film] (Example 1) In the shape of a rectangle, thickness 100 mm PET film, the depth of the groove used is 600 m The insulating coating 1 prepared in Example 1 was applied by a blade coater of 1000 mm. The PET film was kept horizontal and dried in a forced air oven at 70°C for 15 minutes, 90°C for 45 minutes, and 130°C for 10 minutes, to form a film on the PET film. After the film was peeled off from the PET film, it was heat treated at 150°C for 10 minutes, 200°C for 10 minutes, 250°C for 10 minutes, and 300°C for 60 minutes, to obtain an insulating film. It should be noted that the thickness of the obtained insulating film was 55 m m.

[0074] (Example 2) In Example 1, an insulating film was obtained in the same manner except that the insulating coating material 1 was replaced with the insulating coating material 2. It should be noted that the thickness of the obtained insulating film was 56 m m.

[0075] (Example 3) In Example 1, the insulating coating 1 is replaced by the insulating coating 3, and the depth of the groove is replaced by 300 m m, except for this, an insulating film was obtained in the same manner. It should be noted that the thickness of the obtained insulating film was 26 m m.

[0076] (Comparative Example 1) In Example 1, an insulating film was obtained in the same manner except that the insulating coating material 1 was replaced with the insulating coating material 4. It should be noted that the thickness of the obtained insulating film was 49 m m.

[0077] [Evaluation of insulation film characteristics] The following property evaluations were performed on the insulating films obtained in Examples and Comparative Examples.

[0078] <Measurement of dielectric breakdown voltage in dry state and when moisture is absorbed> (Measurement of dielectric breakdown voltage in dry state) The insulating films prepared in Examples 1 to 3 and Comparative Example 1 were cut into rectangular shapes of 18 cm × 26 cm, dried in a constant temperature oven at 120°C for 60 minutes, and then placed in an insulation breakdown voltage measuring device and voltage was applied to measure the insulation breakdown voltage. The measuring device used an insulation breakdown withstand voltage tester (No. 175, manufactured by Yasuda Seiki Co., Ltd.), and the voltage was applied while increasing the voltage at 0.5 V / s, and the voltage at which the breakdown occurred was taken as the insulation breakdown voltage. It should be noted that this test was carried out 5 times, and the average value of the 5 times was taken as the test result.

[0079] (Evaluation of dielectric breakdown voltage during moisture absorption) The insulating films prepared in Examples 1 to 3 and Comparative Example 1 were cut into rectangular shapes of 18 cm × 26 cm, respectively, and stored in a thermostatic chamber at 30°C and a relative humidity greater than 95% for 3 days to allow them to absorb moisture. Next, the sample after moisture absorption was taken out, placed in an insulation breakdown voltage measuring device and voltage was applied to measure the insulation breakdown voltage. The measuring device used an insulation breakdown withstand voltage tester (No. 175, manufactured by Yasuda Seiki Co., Ltd.), and the voltage was applied while boosting the voltage at 0.5 V / s, and the destroyed voltage was taken as the insulation breakdown voltage. It should be noted that this test was carried out 5 times, and the average value of the 5 times was taken as the test result. It should be noted that in order to prevent the sample from drying before taking it out of the thermostatic chamber for measurement, the measurement was started within 3 minutes.

[0080] [Manufacture of insulated wires] Insulated wires (laminated bodies) were produced according to the procedures shown in Examples 4 to 8 and Comparative Example 2 below. Table 3 shows the insulating coatings (coating materials used) used in the respective insulated wires.

[0081] (Example 4) On a copper conductor (copper wire with a diameter of about 1 mm (conductor diameter is described in Table 3)), the insulating coating 1 was baked for about 1 minute while continuously increasing the temperature from 350°C at the inlet to 430°C at the outlet. The above process was repeated 20 times to form a 40 mm thick insulating coating on the surface of the copper conductor. m The insulating layer was 40 m thick and the insulated wire was made using the insulating coating material 1 containing boehmite. m m.

[0082] (Example 5) In Example 4, an insulated wire was produced in the same manner except that the insulating coating 1 was replaced with the insulating coating 2. m m.

[0083] (Example 6) In Example 4, the insulated wire was produced in the same manner except that the insulating coating 1 was replaced with the insulating coating 5. m m.

[0084] (Example 7) In Example 4, an insulated wire was produced in the same manner except that the insulating coating 1 was replaced with the insulating coating 6. m m.

[0085] (Example 8) In Example 4, an insulated wire was produced in the same manner except that the insulating coating 1 was replaced with the insulating coating 7. m m.

[0086] (Comparative Example 2) In Example 4, an insulated wire was produced in the same manner except that the insulating coating 1 was replaced with the insulating coating 4. m m.

[0087] [Evaluation of characteristics of insulated wires] The insulated wires obtained in Examples and Comparative Examples were evaluated for the following properties.

[0088] <Flexibility Evaluation> The flexibility of the insulated wire was tested in accordance with JIS C3216-5-1 winding test.

[0089] <Measurement of Vt characteristic test> The produced insulated wire was subjected to a Vt characteristic test by the following method. The measurement results are shown in Table 3.

[0090] (Dry Vt characteristic test) Using each insulated wire, twisted pair wire samples were prepared according to JIS C 3216, and voltage was applied between the two wires. The measurement environment was set to 40°C, dry air was introduced into the sample measurement constant temperature chamber, and the relative humidity was controlled to be below 30%. It should be noted that the measurement was performed using the inverter pulse generator PG-W03KP-A of Nissin Pulse Electronics Co., Ltd., and the time until the twisted pair wire sample reached insulation breakdown was measured under the following conditions.

[0091] Measurement conditions: voltage 2.5 kVp, pulse width 5 m s, bipolar rectangular wave with a frequency of 10kHz (High humidity (50%RH) Vt characteristic test) Using each insulated wire, twisted pair wire samples were prepared according to JIS C 3216, and voltage was applied between the two wires. The measurement environment was controlled to 25°C and air with a relative humidity of 50% was introduced into the sample measurement chamber, and the relative humidity in the chamber was always controlled to 50%. It should be noted that the measurement was performed using the inverter pulse generator PG-W03KP-A of Nissin Pulse Electronics Co., Ltd., and the time until the twisted pair wire sample reached insulation breakdown was measured under the following conditions.

[0092] Measurement conditions: voltage 2.5 kVp, pulse width 5 m s, bipolar rectangular wave with a frequency of 10kHz (High humidity (70%RH) Vt characteristic test) Using each insulated wire, twisted pair wire samples were prepared according to JIS C 3216, and voltage was applied between the two wires. The measurement environment was controlled to 25°C and air with a relative humidity of 70% was introduced into the sample measurement chamber, and the relative humidity in the chamber was always controlled to 70%. It should be noted that the measurement was performed using the inverter pulse generator PG-W03KP-A of Nissin Pulse Electronics Co., Ltd., and the time until the twisted pair wire sample reached insulation breakdown was measured under the following conditions.

[0093] Measurement conditions: voltage 2.5 kVp, pulse width 5 m s, bipolar rectangular wave with a frequency of 10kHz (High temperature Vt characteristics test) Using each insulated wire, a twisted pair wire sample was prepared according to JIS C 3216, and a voltage was applied between the two wires. The measurement environment was controlled at a temperature of 240°C. It should be noted that the measurement was performed using an inverter pulse generator PG-W03KP-A from Nissin Pulse Electronics Co., Ltd., and the time until the twisted pair wire sample reached insulation breakdown was measured under the following conditions.

[0094] Measurement conditions: voltage 1.5 kVp, pulse width 5 m s, bipolar rectangular wave with a frequency of 10kHz <Measurement of dielectric breakdown voltage in dry state and when moisture is absorbed> The insulation breakdown voltage of the manufactured insulated wire in a dry state and in a moisture-absorbed state were measured by the following method.

[0095] (Measurement of insulation breakdown voltage after drying) Using each insulated wire, a twisted pair sample was made according to JIS C 3216 and dried in a constant temperature bath at 125°C for 30 minutes. Then, the two wires of the twisted pair were connected to a measuring device, a voltage was applied between the two wires, and the insulation breakdown voltage was measured. The measuring device used an insulation breakdown withstand voltage tester (No. 175, manufactured by Yasuda Seiki Co., Ltd.), and a voltage was applied between the two wires while increasing the voltage by 0.5v / s, and the voltage at which the voltage was broken was taken as the insulation breakdown voltage. It should be noted that this test was carried out 5 times, and the average value of the 5 times was taken as the test result.

[0096] (Evaluation of dielectric breakdown voltage during moisture absorption) Using each insulated wire, twisted pair samples were made according to JIS C 3216, and stored in a thermostatic chamber at 40°C and 95% relative humidity for 3 days to allow them to absorb moisture. Next, the sample after moisture absorption was taken out, and the two wires of the twisted pair were connected to a measuring device, and a voltage was applied between the two wires to measure the insulation breakdown voltage. The measuring device used an insulation breakdown withstand voltage tester (No. 175, manufactured by Yasuda Seiki Co., Ltd.), and a voltage was applied between the two wires while increasing the voltage at 0.5V / s, and the voltage at which it was destroyed was taken as the insulation breakdown voltage. It should be noted that in order to prevent the sample from drying out before taking it out of the thermostatic chamber for measurement, the measurement was started within 3 minutes. This test was carried out 5 times, and the average value of the 5 times was taken as the test result.

[0097] [Table 1]

[0098] [Table 2]

[0099] [Table 3]

[0100] Explanation of symbols 10: Laminated body 1: Conductor 2: Insulation coating 3: Insulation layer 4: Insulation layer.

Claims

1. A laminate, characterized in that: At least having a conductor and an insulating film, The insulating film is composed of a nanocomposite material, wherein the nanocomposite material includes a resin composition in which a metal oxide hydrate is dispersed in a resin. The zeta potential of the metal oxide hydrate when dispersed in N-methyl-2-pyrrolidone (NMP) is negative.

2. The laminate according to claim 1, wherein The metal oxide hydrate includes aluminum oxide hydrate.

3. The laminate according to claim 1 or 2, wherein: The nanocomposite material is obtained by dispersing the metal oxide hydrate in a sol state.

4. The laminate according to claim 1 or 2, wherein: The resin contained in the nanocomposite material is at least one selected from the group consisting of formal resin, polyurethane, epoxy resin, polyester, polyesterimide, polyetherimide, polyamideimide, polyimide and precursors thereof.

5. The laminate according to claim 1 or 2, wherein: The resin contained in the nanocomposite material is at least one selected from the group consisting of polyimide and a precursor of polyimide.

6. The laminate according to claim 1 or 2, wherein: The laminated body is in the form of an insulated wire.

7. A coil, characterized in that: A laminate comprising the layered product according to claim 6.

8. A rotating electrical machine, characterized in that: A laminate comprising the layered product according to claim 6.

9. An insulating resin composition, characterized in that: The insulating film is used to form the laminated body according to claim 1 or 2.

10. An insulating coating, characterized in that: The insulating film is used to form the laminated body according to claim 1 or 2.

11. An insulating film, characterized in that: It is formed by the nanocomposite material according to claim 1 or 2.